(untitled) - Gosling, Mary (Canberra, Australia, 2000)
This book covers knowledge and skills needed by anyone working in a library or other information agency. It contents: nature and uses of information; the information industry ( Libraries ); different library environments; networks...
Keywords: Information science,Information services,Library science